ANALISIS PENGARUH MANAJEMEN LABA TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY DENGAN CORPORATE GOVERNANCE SEBAGAI VARIABEL MODERASI (Studi Empiris pada Perusahaan Sektor Consumer Non-Cyclical yang Terdaftar di Bursa Efek Indonesia Periode 2022–2024) - Amabel Shafa Rasendriya Wijanarko; Marsono Marsono (Diponegoro Journal of Accounting, 2026)
This study examines the effect of earnings management on Corporate Social Responsibility (CSR) disclosure and investigates the moderating role of corporate governance in this relationship. The population consists of consumer non-cyclical companies listed on the Indonesia Stock Exchange during the period 2022–2024. Samples were selected using purposive sampling, resulting in 114 firm-year observations. CSR disclosure was measured using content analysis based on 117 disclosure items from the Global Reporting Initiative (GRI) Standards 2021. Earnings management was proxied by discretionary accruals calculated using the Modified Jones Model. Corporate governance was proxied by board of commissioners size, board meeting frequency, managerial ownership, institutional ownership, and audit committee size. Data were analyzed using Moderated Regression Analysis (MRA). The results indicate that earnings management has a positive and significant effect on CSR disclosure. Furthermore, board of commissioners size significantly weakens the relationship between earnings management and CSR disclosure. However, board meeting frequency, managerial ownership, institutional ownership, and audit committee size do not significantly moderate the relationship. These findings support agency theory, legitimacy theory, and stakeholder theory in explaining corporate disclosure behavior.